Evaluation Of The Implementation Of The Youth Program For Rural Development Movement At The Youth And Sports Department Of The Regional Government Of Riau Province In 2016 - Hendy Selwa; Syafrinaldi Syafrinaldi (UIR Press, 2022)
The phenomenon in this study is the placement of PSP-3 participants, the activities of PSP-3 participants and the Cost of Living for PSP-3participants that have not been implemented in accordance with the stages of program implementation and guidebooks for implementing the PSP-3 program. The purpose of this study was to find out and analyze the Implementation of the Rural Development Program for Youth Development in the Department of Youth and Sports of the Regional Government of Riau Province in 2016, and to find out the obstacles or symptoms that made the implementation of the Bachelor Youth Program Driving Rural Development in the Youth Service and Sport of the Provincial Government of Riau in 2016. The indicators of assessment in the study of the Evaluation of the Implementation of the Undergraduate Youth Program Driving Rural Development in the Department of Youth and Sports of the Provincial Government of Riau in 2016 include Inputs, Processes, Outputs, Income. And this study uses Qualitative research methods, namely prioritizing interview lists, documentation as a tool for collecting data and data collected with this tool and then used as the main raw material to analyze the empirical conditions of the objectivity of the existence of research objectives at the meticulous location. The population in this study included the Head of the Riau Province Youth and Sports Office, the Head of the Youth Division of the Riau Province Youth and Sports Office, the Head of the Siak Regency Youth and Sports Office, the Kampung Tengah Village Head, the Mempura River Village and PSP-3 Participants in Siak Regency. Based on the results of the study assessing and concluding that the Evaluation of the Implementation of the Undergraduate Youth Driving Program in Rural Development at the Office of Youth and Sports of the Regional Government of Riau Province in 2016 was in the assessment of Not Implemented Well.